Identification of FDA‐approved drugs as novel allosteric inhibitors of human executioner caspases. Issue 11 (5th October 2018) - Krishna Deepak, R. N. V.; Abdullah, Ahmad; Talwar, Priti; Fan, Hao; Ravanan, Palaniyandi
Abstract: The regulation of apoptosis is a tightly coordinated process and caspases are its chief regulators. Of special importance are the executioner caspases, caspase‐3/7, the activation of which irreversibly sets the cell on the path of death. Dysregulation of apoptosis, particularly an increased rate of cell death lies at the root of numerous human diseases. Although several peptide‐based inhibitors targeting the homologous active site region of caspases have been developed, owing to their non‐specific activity and poor pharmacological properties their use has largely been restricted. Thus, we sought to identify FDA‐approved drugs that could be repurposed as novel allosteric inhibitors of caspase‐3/7. In this study, we virtually screened a catalog of FDA‐approved drugs targeting an allosteric pocket located at the dimerization interface of caspase‐3/7. From among the top‐scoring hits we short‐listed 5 compounds for experimental validation. Our enzymatic assays using recombinant caspase‐3 suggested that 4 out of the 5 drugs effectively inhibited caspase‐3 enzymatic activity in vitro with IC50 values ranging ~10‐55 μM. Structural analysis of the docking poses show the 4 compounds forming specific non‐covalent interactions at the allosteric pocket suggesting that these molecules could disrupt the adjacently‐located active site. In summary, we report the identification of 4 novel non‐peptide allosteric inhibitors of caspase‐3/7 from among FDA‐approved drugs.